Avaliação de Técnicas de Teste para Dispositivos Móveis por Meio de Experimentação - DEUS, Gilcimar Divino de (2009)
Software quality is aimed at for every person that works with computation. Many techniques, methods and tools have been proposed helping us to get high level software quality. Due to the increase in the number of mobile devices available daily, there is a high number of software products for such devices are under development. To test the software for mobile devices it is important to know the characteristics of both the device and the software itself aiming at to get high quality products. One package of experimentation aiming at evaluating some well known testing techniques applied in mobile software is proposed. This work describe the proposed package, the results obtained after three replications, and highlight which technique is more adequate for grant quality in Java ME software. The replications occur in a controlled environment, producing a consistent information database about the usage of the testing techniques in JavaME programs. New replications can be carried out for collecting more data and increasing the confidence in the results obtained so far. The final objective, after many replications, is to develop one incremental strategy for testing Java ME software. A preliminary version of this strategy is presented in this work and can be further refined. Moreover, the data obtained during the experiment helps improving the JaBUTi/ME testing tool, aiming at to maximize the support and reduce the cost of the testing activity